Penerapan alat permainan edukatif (APE) dalam pembelajaran kelas rendah: studi kasus di MI Ma'arif Mulyasari 1 - Siti Uswatun Hasanah; Johar Alimuddin; Rina Rizki Amalia (Indonesian Journal of Learning and Educational Studies, 2026)
This study aims to deeply analyze the implementation of Educational Teaching Aids (APE) in lower-grade learning at MI Ma'arif 1 Mulyasari and evaluate its impact on student learning development. Using a qualitative descriptive approach, the research subjects involved 5 classroom teachers and 109 students. Data were collected through observation, interviews, and documentation. The results indicate that the mapping of APE typology is carried out in an adaptive tiered manner matching the cognitive structure of the concrete operational phase of children aged 7–9 years. Data analysis carried out qualitatively refers to the Miles and Huberman model, namely data reduction, data presentation, drawing conclusions. The successful implementation of the media is supported by systematic teacher instructional management through curricular planning, interactive execution based on a "Playing Rule Contract," and independent formative evaluation. Integrating APE brings significant multidimensional impacts: increasing classical learning completeness (an increase gap of 17% to 30%), extending attention span in class, and reducing social conflict among students by 75% while fostering prosocial behavior. The novelty of this research lies in the utilization of local recycled materials with hot lamination technical reinforcement, which successfully solves the durability issue of teaching aids, creating waterproof and high-durability media.